2016
DOI: 10.1002/clc.22638
|View full text |Cite
|
Sign up to set email alerts
|

Trends in hospitalization for congestive heart failure, 1996–2009

Abstract: Background: Although heart failure (HF) is a common cause of hospital admissions, few data describe temporal trends in HF hospitalization. We present data on number of HF admissions, length of stay (LOS), and inpatient mortality in the United States, 1996-2009. Hypothesis:To assess HF hospitalizations in a national sample of United States population.Methods: Data were obtained from the National Hospital Discharge Survey (NHDS), a national probability sample survey of discharges conducted annually by the Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…More than 7 million Europeans suffer from heart failure (HF), which has become the leading cause of hospitalization . Both systolic dysfunction (SD) and diastolic dysfunction (DD) are acknowledged important prognostic markers of morbidity and mortality risk . Several studies documented an important role of DD on the development and course of heart failure with preserved ejection fraction (HFpEF), whereas such a modifying role in subjects with heart failure with reduced ejection fraction (HFrEF) is less well documented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 7 million Europeans suffer from heart failure (HF), which has become the leading cause of hospitalization . Both systolic dysfunction (SD) and diastolic dysfunction (DD) are acknowledged important prognostic markers of morbidity and mortality risk . Several studies documented an important role of DD on the development and course of heart failure with preserved ejection fraction (HFpEF), whereas such a modifying role in subjects with heart failure with reduced ejection fraction (HFrEF) is less well documented.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Both systolic dysfunction (SD) and diastolic dysfunction (DD) are acknowledged important prognostic markers of morbidity and mortality risk. [3][4][5] Several studies documented an important role of DD on the development and course of heart failure with preserved ejection fraction (HFpEF), 4,6,7 whereas such a modifying role in subjects with heart failure with reduced ejection fraction (HFrEF) is less well documented. A study from Japan reported that the risk of hospital readmission and death increased with progressive DD in 126 patients with Author contributions: Hans-Dirk Düngen, MD, and Stefan Störk, MD, contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…Decompensated heart failure (HF) is the most common cause of hospital admission among the Centers for Medicare and Medicaid Services’ (CMS) population, comprising more than half of the national cost of HF care . In an effort to improve the quality of care and reduce preventable HF admissions, CMS initiated the Hospital Readmission Reduction Program (HRRP) in October 2012, which imposes a percentage reduction in Medicare base reimbursements to hospitals underperforming based on their 3‐year risk‐standardized all‐cause 30‐day readmission rate following an index HF admission . Although an unintended consequence of the HRRP's financial incentives, hospitals often use the CMS HRRP report as the sole benchmark for defining and quantifying their HF admission population and making quality‐improvement decisions without understanding the methodology or the inclusion and exclusion criteria of the HRRP HF report .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In an effort to improve the quality of care and reduce preventable HF admissions, CMS initiated the Hospital Readmission Reduction Program (HRRP) in October 2012, which imposes a percentage reduction in Medicare base reimbursements to hospitals underperforming based on their 3-year risk-standardized all-cause 30-day readmission rate following an index HF admission. [5][6][7] Although an unintended consequence of the HRRP's financial incentives, hospitals often use the CMS HRRP report as the sole benchmark for defining and quantifying their HF admission population and making quality-improvement decisions without understanding the methodology or the inclusion and exclusion criteria of the HRRP HF report. [8][9][10] The CMS HF admission definition used in the HRRP requires a primary discharge International Classification of Diseases (ICD) HF diagnostic code in addition to satisfying several significant inclusion and exclusion criteria ( Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in care have failed to stem a rising tide of heart failure‐related hospital admissions. Annually, heart failure is the primary reason for >200 000 admissions in Japan, >80 000 in the United Kingdom (UK) and about one million in the United States of America (USA) . Despite advances in the management of chronic heart failure, mortality amongst patients hospitalized with worsening heart failure remains high, and no intervention has been convincingly shown to improve outcome …”
Section: Introductionmentioning
confidence: 99%